2013
DOI: 10.1111/pbi.12121
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic expression of a BZR1‐1D transcription factor in brassinosteroid signalling enhances carotenoid accumulation and fruit quality attributes in tomato

Abstract: SummaryThe brassinosteroid (BR) response transcription factor Brassinazole resistant 1 (BZR1)-mediated BR signalling regulates many specific developmental processes including fruit ripening. Here, we report the effect of 2,4-epibrassinolide (EBR) and BZR1-1D overexpression on carotenoid accumulation and quality attributes of tomato (Solanum lycopersicum) fruit. EBR-treated pericarp discs of ethylene-insensitive mutant, Never ripe, accumulated significantly more carotenoid than those of the control. The results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
86
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(96 citation statements)
references
References 53 publications
9
86
1
Order By: Relevance
“…Several studies implicate phytohormones in mediating fruit chloroplast development in tomato, and in the case of auxin and BRs enhanced fruit chloroplast development is positively correlated with increased SlGLK expression (Martineau et al ., ; Galpaz et al ., ; Sagar et al ., ; Liu et al ., ). In addition, auxin gradients are involved in several developmental processes, and disruption of auxin signaling in the arf6 / arf8 double mutant results in ectopic KNOX expression and altered floral morphology (Benkova et al ., ; Petersson et al ., ; Tabata et al ., ).…”
Section: Resultsmentioning
confidence: 98%
“…Several studies implicate phytohormones in mediating fruit chloroplast development in tomato, and in the case of auxin and BRs enhanced fruit chloroplast development is positively correlated with increased SlGLK expression (Martineau et al ., ; Galpaz et al ., ; Sagar et al ., ; Liu et al ., ). In addition, auxin gradients are involved in several developmental processes, and disruption of auxin signaling in the arf6 / arf8 double mutant results in ectopic KNOX expression and altered floral morphology (Benkova et al ., ; Petersson et al ., ; Tabata et al ., ).…”
Section: Resultsmentioning
confidence: 98%
“…Significantly, we found that BR levels were closely related to the accumulation of phytoene, phytofluene, β‐carotene and lycopene (Table ). Foliar application of exogenous BRs and ectopic expression of a BZR1‐1D transcription factor in BR signalling could enhance carotenoid accumulation in tomato (Liu et al ., ; Zhu et al ., ). Therefore, BRs are actively involved in the regulation of fruit carotenoid metabolism and manipulation of BR biosynthesis, or their signalling is a potential approach to improve fruit quality in tomato.…”
Section: Discussionmentioning
confidence: 99%
“…) by mutation, gene silencing or knockouts, or overexpression of either the target genes or the individual transcription factors (often ERFs) that regulate them (Grierson, ; M. C. Liu et al ., , ; Xie et al ., ). Ethylene also is effective when applied externally to mature fruit, which provides a very convenient experimental switch, but ripening is probably also influenced by the balance of other hormones including abscisic acid (ABA) (Zhang et al ., ; Ma et al ., ), auxin (Audran‐Delalande et al ., ) and brassinosteroids (L. H. Liu et al ., ).…”
Section: The Importance Of Ethylene In Controlling Ripeningmentioning
confidence: 97%